STRATEGI KEPUASAN PELANGGAN CORPORATE UNTUK MENINGKATKAN REPUTASI PERUSAHAAN PT. MORATELINDO - Budiman, John; Sihite, Mombang; Zulkifli (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2022)
The purpose of this study was to determine the effect of service quality and customer value on company reputation directly or indirectly through customer satisfaction, and the influence of customer value on customer satisfaction moderated by service innovation at PT. Moratelindo. The research sample was 205 respondents who are non-retail customers of PT. Moratelindo. Data collection using questionnaire and forum group discussion (FGD). Data analysis techniques used Structural Equation Modeling (SEM) analysis which was processed with SmartPLS software version 3. The results of the study prove that service quality variables have a significant effect on customer satisfaction and corporate reputation. The customer value variable has a significant effect on customer satisfaction and corporate reputation. The customer satisfaction can be the mediator for service quality and customer value to give a signinficant effect on corporate reputation. Service innovation variable is not able to encourage or strengthen the influence of customer value on customer satisfaction at PT. Moratelindo.